Extreme wettability of nanostructured glass fabricated by non-lithographic, anisotropic etching - Yu, Eusun; Kim, Seul-Cham; Lee, Heon Ju; Oh, Kyu Hwan; Moon, Myoung-Woon (NATURE PUBLISHING GROUP, 2015)
Functional glass surfaces with the properties of superhydrophobicity/or superhydrohydrophilicity, anti-condensation or low reflectance require nano-or micro-scale roughness, which is difficult to fabricate directly on glass surfaces. Here, we report a novel non-lithographic method for the fabrication of nanostructures on glass; this method introduces a sacrificial SiO2 layer for anisotropic plasma etching. The first step was to form nanopillars on SiO2 layer-coated glass by using preferential CF4 plasma etching. With continuous plasma etching, the SiO2 pillars become etch-resistant masks on the glass; thus, the glass regions covered by the SiO2 pillars are etched slowly, and the regions with no SiO2 pillars are etched rapidly, resulting in nanopatterned glass. The glass surface that is etched with CF4 plasma becomes superhydrophilic because of its high surface energy, as well as its nano-scale roughness and high aspect ratio. Upon applying a subsequent hydrophobic coating to the nanostructured glass, a superhydrophobic surface was achieved. The light transmission of the glass was relatively unaffected by the nanostructures, whereas the reflectance was significantly reduced by the increase in nanopattern roughness on the glass.
Keywords: SUPERHYDROPHILIC SURFACES; TRANSPARENT; FILMS; COATINGS; PLASMA; QUARTZ; SIO2